Mhairi's Dilemma - Barbara Mullin; Mhairi Mullin; Roger Mullin; Jack Dowie; Rex V. Brown (Judgment and Decision Making, 2008)
A case study review of a formal decision analysis involving a 10 year old girl. She had just faced the death of a close adult friend, and had become filled with uncertainty and emotion while facing the decision as to whether or not to attend his funeral. The study demonstrates that formal analysis can provide the sensitivity and caring basis for such decision making, thus counteracting some of the criticisms of decision analysis.